2002
DOI: 10.2166/wst.2002.0460
|View full text |Cite
|
Sign up to set email alerts
|

Dispelling the “Nocardia amarae” myth: a phylogenetic and phenotypic study of mycolic acid-containing actinomycetes isolated from activated sludge foam

Abstract: Right-angle branched filaments and rods micromanipulated from activated sludge foam and mixed liquor were identified as putatively novel members of the genera Gordonia, Mycobacterium and Rhodococcus using a combination of chemical, molecular and morphological data. Pyrolysis mass spectrometric analyses of gordoniae isolated in both the present and a previous study revealed pyro-groups, distinct from validly described Gordonia species, which could be equated with those based on morphological properties and 16S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 26 publications
3
14
0
2
Order By: Relevance
“…The pale beige to peach colonies contained meso-diaminopimelic acid and N-glycolated muramic acid in the peptidoglycan, arabinose and galactose in the whole cell hydrolysate, and dehydrogenated menaquinones with nine isoprene units as the predominant isoprenologue, properties consistent with the classification of the organism in the genus Gordonia [3]. The organism also contained mycolic acids, the methyl esters of which had the same Rf value as Gordonia marker strains.…”
Section: Taxonomy Of the Producing Strainsupporting
confidence: 68%
See 1 more Smart Citation
“…The pale beige to peach colonies contained meso-diaminopimelic acid and N-glycolated muramic acid in the peptidoglycan, arabinose and galactose in the whole cell hydrolysate, and dehydrogenated menaquinones with nine isoprene units as the predominant isoprenologue, properties consistent with the classification of the organism in the genus Gordonia [3]. The organism also contained mycolic acids, the methyl esters of which had the same Rf value as Gordonia marker strains.…”
Section: Taxonomy Of the Producing Strainsupporting
confidence: 68%
“…Extracts were generated from culture filtrates and mycelia at various fermentation times and their secondary metabolite profiles evaluated by HPLC-diode array analysis and an in-house developed HPLC-UV-Vis database [2]. Strain Acta 2299, which was isolated from activated sludge foam [3] near Bendigo (Victoria, Australia), was of particular interest because of the appearance of two characteristic metabolites in HPLC runs of the culture filtrate extract at retention times of 8.1 and 9.3 minutes, respectively, in our standardized gradient elution profile. Their UV-visible spectra were not congruent with any of the 867 reference compounds stored in the database.…”
Section: Introductionmentioning
confidence: 99%
“…Members of these taxa can be distinguished from one another using a combination of chemotaxonomic and morphological properties, and form distinct lineages in the Corynebacterineae 16S rRNA gene tree. Activated sludge wastewater-treatment plants with foaming problems (Soddell, 1999) are a rich source of mycolic-acid-containing actinomycetes (Lemmer & Kroppenstedt, 1984;Soddell & Seviour, 1990, 1995Goodfellow et al, 1998b;Stainsby et al, 2002), as exemplified by Gordonia amarae (Lechevalier & Lechevalier, 1974) Klatte et al 1994, Skermania piniformis Chun et al 1997, Tsukamurella pseudospumae Nam et al 2004 and Tsukamurella spumae Nam et al 2003. Two actinomycetes that showed rudimentary right-angled branching and which produced salmon-pink filamentous colonies were isolated from activated sludge foam by using a micromanipulator (Soddell & Seviour, 1994). Subsequent studies based on numerical taxonomic and preliminary 16S rRNA gene sequence data indicated that the two strains, isolates J81 T and J82, might represent a novel genus in the suborder Corynebacterineae , a proposition underpinned by the results of the present investigation.…”
mentioning
confidence: 99%
“…However, it is clear that many additional mycolic acidcontaining taxa associated with foam need to be formally described (Soddell & Seviour, 1998;Stainsby et al, 2002). Such studies are important, as attempts to control the appearance and persistence of foams are unlikely to succeed until the taxonomic diversity and functional roles of the causal organisms are understood (Goodfellow et al, 1996(Goodfellow et al, , 1998Stainsby et al, 2002).Three isolates with a cellular morphology intermediate between the right-angled branching pattern typical of G. amarae Klatte et al 1994 and the 'pine-tree-like' morphotype of Skermania piniformis Chun et al 1997 were isolated, by micromanipulation, in Australia from activated sludge foams at Brimbank Park, Victoria (isolates J4 T and J5) and Craigieburn, Victoria (isolate J59), as described by Soddell & Seviour (1998). These authors considered that the strains might form a novel species on the basis of an extensive numerical taxonomic survey of Skermania and related strains, a proposition underpinned by the results of the present investigation.…”
mentioning
confidence: 99%
“…Novel species isolated from foams include members of the genera Nocardia (Yamamura et al, 2005) and Tsukamurella (Nam et al, 2003(Nam et al, , 2004. However, it is clear that many additional mycolic acidcontaining taxa associated with foam need to be formally described (Soddell & Seviour, 1998;Stainsby et al, 2002). Such studies are important, as attempts to control the appearance and persistence of foams are unlikely to succeed until the taxonomic diversity and functional roles of the causal organisms are understood (Goodfellow et al, 1996(Goodfellow et al, , 1998Stainsby et al, 2002).…”
mentioning
confidence: 99%